PENGARUH PARTISIPASI ANGGARAN, KEJELASAN TUJUAN SASARAN ANGGARAN TERHADAP KINERJA MANAJERIAL DENGAN KOMITMEN ORGANISASI SEBAGAI VARIABEL MODERATING (Studi Empiris Pada SKPD Kabupaten Rokan Hilir - Permana, Indra; Kamaliah, Kamaliah; Ilham, Elfi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
This study aims to examine the effect of Budgeting Participation, Budgetary Goal Clarity on the Managerial Performance and Organizational Commitment as a moderating variable in the District Government of Rokan HIlir.The population in this study is the Regional Task Force (SKPD), SKPD treasurer, and financial staff SKPD Rokan Hilir district, using a questionnaire survey. The data was collected by distributing questionnaires to 76 respondents, but only 69 respondents who fill out questionnaires. Methods of data analysis using Multiple Linear Regression Analisys who assisted with SPSS software. Results shows that budgetting participation has effect to the Manajerial Performance, Budgetary Goal Clarity has effect to the Manajerial Performance, and organizational commitment has moderated the effect of budgetting participation and Budgetary Goal Clarity on Managerial Performance.Keywords : Participation, Budgetary Goal Clarity, Commitment, and Manajerial Performance.